Yeast applied readthrough inducing system (YARIS): an invivo assay for the comprehensive study of translational readthrough - Beznosková, Petra; Pavlíková, Zuzana; Zeman, Jakub; Echeverría Aitken, Colin; Valášek, Leoš S (Nucleic acids research, 2019)
Stop codon readthrough-the decoding of a stop codon by a near-cognate tRNA-is employed by viruses to balance levels of enzymatic and structural proteins and by eukaryotic cells to enable isoform-specific protein synthesis in response to external stimuli. Owing to the prevalence of premature termination codons in human disease, readthrough has emerged as an attractive therapeutic target. A growing list of various features, for example the +4 nucleotide immediately following the stop codon, modulate readthrough levels, underscoring the need for systematic investigation of readthrough. Here, we identified and described a complete group of yeast tRNAs that induce readthrough in the stop-codon tetranucleotide manner when overexpressed, designated readthrough-inducing tRNAs (rti-tRNAs). These rti-tRNAs are the keystones of YARIS (yeast applied readthrough inducing system), a reporter-based assay enabling simultaneous detection of readthrough levels at all twelve stop-codon tetranucleotides and as a function of the complete set of rti-tRNAs. We demonstrate the utility of YARIS for systematic study of translation readthrough by employing it to interrogate the effects of natural rti-tRNA modifications, as well as various readthrough-inducing drugs (RTIDs). This analysis identified a variety of genetic interactions demonstrating the power of YARIS to characterize existing and identify novel RTIDs.
Keywords: nukleotidy; terminační kodon; Saccharomyces cerevisiae; RNA, Transfer, Gln; RNA, Transfer, Tyr; Protein Biosynthesis; proteosyntéza; Codon, Terminator; Nucleotides; RNA transferová; Aminoglycosides; RNA, Transfer; RNA transferová Tyr; RNA transferová Gln; aminoglykosidy